2023
DOI: 10.3390/ijms24021570
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structural and Sensor Properties of Nanosized Mixed Oxides Based on In2O3 Particles

Abstract: The paper considers the relationship between the structure and properties of nanostructured conductometric sensors based on binary mixtures of semiconductor oxides designed to detect reducing gases in the environment. The sensor effect in such systems is determined by the chemisorption of molecules on the surface of catalytically active particles and the transfer of chemisorbed products to electron-rich nanoparticles, where these products react with the analyzed gas. In this regard, the role is evaluated of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
3
0
Order By: Relevance
“…The magnitude of the sensor response of hydrothermal ZnO-In 2 O 3 composites containing up to 20% zinc oxide is significantly influenced by the fact that during the synthesis of such composites, a change in the phase composition of In 2 O 3 , namely the transition of the cubic to the rhombohedral phase, occurs. Earlier, we found that the introduction of cerium into indium oxide, leading to its phase changes, causes a sharp drop in the sensor response to hydrogen compared with pure indium oxide [ 36 ]. The introduction of zinc into cubic indium oxide also leads to an increase in the response to NO 2 compared with the undoped sample [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of the sensor response of hydrothermal ZnO-In 2 O 3 composites containing up to 20% zinc oxide is significantly influenced by the fact that during the synthesis of such composites, a change in the phase composition of In 2 O 3 , namely the transition of the cubic to the rhombohedral phase, occurs. Earlier, we found that the introduction of cerium into indium oxide, leading to its phase changes, causes a sharp drop in the sensor response to hydrogen compared with pure indium oxide [ 36 ]. The introduction of zinc into cubic indium oxide also leads to an increase in the response to NO 2 compared with the undoped sample [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 , 8 , 9 , 10 , 11 , 12 ]). The most important types of interaction affecting the sensor response in binary nanosystems include the transfer of atomic oxygen between catalytically active and electron-rich nanoparticles, as well as the introduction of ions of particles of one oxide into the other component [ 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nanostructured metal oxides have emerged as promising materials for sensor applications due to their ability to modulate conductivity in response to trace concentrations of gases in the atmosphere. These sensors have demonstrated efficacy in detecting various pollutants, including toxic gases and volatile organic complexes in the air, such as ammonia, CO, NO2, H2, benzene, methane, and ethanol Wang et al 2021;Hu et al 2018;Wang et al 2022;Han et al 2015;Ikim et al 2023]. The metal oxides, such as indium oxide (In2O3), stand out for their favorable properties, such as a small band gap, high electron concentration, and mobility [Nunes et al 2019;Wang et al 2018].…”
Section: Introductionmentioning
confidence: 99%